The measurement and quality of human whole body centre of mass location data - McKinon, Warrick (My University, 2008)
Since its first measurement in 1679, the usefulness of the location of whole body centre of mass (COM) data has progressed from having largely theoretical value into being an instrument with several diagnostic and applied scientific uses. This thesis describes first the biomechanical and measurement theory foundation of COM research and then details the historical development of methods to measure COM location and the various applied uses of this variable. Original research data presented in this thesis then go on to provide the first direct measurements of COM movement in walking humans. A second study quantifies the accuracy of the most commonly used current technique to quantify COM location (the kinematic segmental method) by determining the limits of agreement between it and a direct measurement method (the reaction-board), in lying and running subjects. In the latter studies a novel reaction-board measurement method is developed making use of life-sized projections of subjects in various stride positions and used to place runners into recumbent static running positions. These data demonstrate that reaction-board and segmental methods report COM locations with a mean difference of 1.6cm and agree to within limits of 6.0cm for the location of COM in recumbent individuals. The final study described in this thesis compares single COM measurements made using two kinematic segmental methods (models) to a direct suspension technique of measuring COM location. The suspension technique used is adapted from the original method of determining COM location upon which kinematic segmental methods derive their origin. The data show that both cadaver-derived kinematic models of COM, and kinematic models derived from live human data, differ from a direct COM suspension method, and that cadaver based estimates display greater accuracy (agreement with the direct suspension method). This study also uniquely provides information on the effect of whole body mass, body fat or body water on the accuracy of segmental models in male subjects.
Keywords: biomechanics; center of gravity; walking; running